Effects of organizational change on firm productivity - Christina Håkanson (Sveriges Riksbank, 2009)
An increasing use of IT facilitates firms to use more efficient organizational forms. Significant reorganizations of business processes around IT capital can thereby boost productivity growth. The aim of this study is to empirically examine how firm productivity growth is affected by organizational changes and investments in IT using a Difference-in-Difference approach on a panel of Swedish firms over the years 1997-2005. The empirical results show a positive and significant effect on total factor productivity growth for firms that invested above median in IT and at the same time undertook organizational changes.
Keywords: D24; E22; L22; O33; 330; information technology; productivity; organizational change; Organisatorischer Wandel; Betriebliches Informationssystem; Produktivität; Schweden